Belief Revision in the GOAL Agent Programming Language. (5th September 2013) - Spurkeland, Johannes Svante; Jensen, Andreas Schmidt; Villadsen, Jørgen
Abstract : Agents in a multiagent system may in many cases find themselves in situations where inconsistencies arise. In order to properly deal with these, a good belief revision procedure is required. This paper illustrates the usefulness of such a procedure: a certain belief revision algorithm is considered in order to deal with inconsistencies and, particularly, the issue of inconsistencies, and belief revision is examined in relation to the GOAL agent programming language.